Clinical epidemiological characteristics of mycetoma in Eastern Sennar locality, Sennar State, Sudan - Hassan, Rowa; Deribe, Kebede; Fahal, Ahmed Hassan; Newport, Melanie; Bakhiet, Sahar (PLOS Neglected Tropical Diseases, 2021)
Mycetoma epidemiological features remain uncharacterised. Few studies have been conducted in a community-based setting to explore the epidemiological features and risk factors for mycetoma in Sudan. To bridge this gap, this study was conducted in Eastern Sennar Locality, Sennar State, Sudan, to report the clinical, epidemiological characteristics of mycetoma patients and the disease burden in the state. We used cluster sampling; sixty villages were randomly selected across the locality’s five administrative units, and a household-to-household survey was conducted. We collected data using pre-designed questionnaires at the community, household, and individual levels. We performed descriptive analyses of the data and produced prevalence maps using ArcGIS 10.5 ([ESRI] Inc., Redlands CA, USA). A total of 41,176 individuals were surveyed, and 359 mycetoma patients were identified. The overall prevalence of mycetoma was 0.87% (95%CI = 0.78–0.97%), the prevalence among males was 0.83% (95%CI = 0.71–0.96%), and females 0.92% (95% CI = 0.79–1.06%). Individuals in the age group 31–45 years had the highest prevalence among the different age groups (1.52%, 95% CI = 1.23–1.86%). The prevalence map showed patients clustered within the central and north-eastern part of the locality, while villages in the south-western part had few or no cases. In conclusion, this clinical epidemiological study is pioneering and shows that mycetoma is prevalent in certain parts of Sudan. This data obtained will support the design of measures to reduce the disease burden in the state. The survey procedures and protocols can be adopted for further studies in Sudan and beyond.